Detailed structure of the outer disk around HD 169142 with polarized light in H-band. (11th August 2015) - Momose, Munetake; Morita, Ayaka; Fukagawa, Misato; Muto, Takayuki; Takeuchi, Taku; Hashimoto, Jun; Honda, Mitsuhiko; Kudo, Tomoyuki; Okamoto, Yoshiko K.; Kanagawa, Kazuhiro D.; Tanaka, Hidekazu; Grady, Carol A.; et al.
Abstract : Coronagraphic imagery of the circumstellar disk around HD 169142 in H -band polarized intensity (PI) with Subaru/HiCIAO is presented. The emission scattered by dust particles at the disk surface in 0^′′_. 2 ≤ r ≤ 1^′′_. 2, or 29 ≤ r ≤ 174 au, is successfully detected. The azimuthally averaged radial profile of the PI shows a double power-law distribution, in which the PIs in r = 29–52 au and r = 81.2–145 au respectively show r −3 dependence. These two power-law regions are connected smoothly with a transition zone (TZ), exhibiting an apparent gap in r = 40–70 au. The PI in the inner power-law region shows a deep minimum whose location seems to coincide with the point source at λ = 7 mm. This can be regarded as another sign of a protoplanet in the TZ. The observed radial profile of the PI is reproduced by a minimally flaring disk with an irregular surface density distribution, an irregular temperature distribution, or with a combination of both. The depletion factor of surface density in the inner power-law region ( r < 50 au) is derived to be ≥ 0.16 from a simple model calculation. The obtained PI image also shows small-scale asymmetries in the outer power-law region. Possible origins for these asymmetries include corrugation of the scattering surface in the outer region, and a shadowing effect by a puffed-up structure in the inner power-law region.